Impact of Type and Duration of Application of Commercially Available Oral Moisturizers on Their Antifungal Effects. Issue 1 (24th February 2016) - Murakami, Mamoru; Fujishima, Kei; Nishi, Yasuhiro; Minemoto, Yoko; Kanie, Takahito; Taguchi, Norihiro; Nishimura, Masahiro
Abstract: Purpose: To examine the impact of oral moisturizer type and application time on antifungal effects. Materials and Methods: Seventeen oral moisturizers (7 liquids, 10 gels) and amphotericin B (AMPH‐B) were tested. Antifungal effects were evaluated with newly opened moisturizer samples (0 hour) and with samples incubated for 8 hours to simulate contact during sleep. Candida albicans samples (10 8 cells/ml) were placed into cylindrical holes in 50% trypticase soy agar plates. Antifungal effects were evaluated based on growth‐inhibitory zones after 24 hours. Equal quantities of moisturizers showing growth‐inhibitory zones were mixed as additional samples. The effects of moisturizer type and application time on growth‐inhibitory zones were evaluated with ANOVA. Growth‐inhibitory zone sizes were compared with multiple comparisons. Results: Growth‐inhibitory zones were found with two liquids, one gel, moisturizer mixtures, and AMPH‐B. Significant differences in antifungal effects were found among different moisturizer types and between the 0‐ and 8‐hour groups. The growth‐inhibitory zones of the 8‐hour group were significantly smaller than those of the 0‐hour group. In both the 0‐ and 8‐hour groups, the growth‐inhibitory zones of the liquid‐gel mixtures were significantly larger than those of other moisturizer types, and were the same size as those of AMPH‐B at two concentrations (1.25 and 2.5 μg/ml). Growth‐inhibitory zones of individual moisturizers and liquid‐liquid mixtures were the same size as those of lower AMPH‐B concentrations (0.16, 0.31, and 0.63 μg/ml). Conclusion: Our findings suggest that mixing liquid and gel moisturizers improves their antifungal efficiency.